A temporary VAT cut as unconventional fiscal policy - Ruediger Bachmann; Benjamin Born; Olga Goldfayn-Frank; Georgi Kocharkov; Ralph Luetticke; Michael Weber (Deutsche Bundesbank, 2025)
We exploit Germany's temporary three-percentage-point VAT cut in the second half of 2020 to study the spending response to unconventional fiscal policy. We use survey and scanner data on household consumption expenditures and their perceived pass-through of the tax change into prices, and a RANK model to quantify the effects of this VAT policy. The survey and scanner data show that the temporary VAT reduction led to a relative increase in durable and, to a lesser extent, semidurable spending for individuals with high perceived pass-through. According to the RANK model, the VAT policy increased total aggregate consumption spending by 4.4 percent on impact.
Keywords: D12; E20; E21; E62; E65; R31; 330; unconventional fiscal policy; value added tax; survey data; expectations; consumption; durables; RANK model